PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WAJIB PAJAK DALAM PENERBITAN SURAT TANDA NOMOR KENDARAAN DI SAMSAT BALIKPAPAN - Jarot Prianggono; Dax E.S. Manupputy (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
The study is to examine the influence of service quality to satisfaction of taxpayers in the issuance of registration plates of vehicle (STNK) in SAMSAT Balikpapan. The purposes of this study are: (1) to know the effect of service quality provided to the satisfaction of taxpayer, (2) to know how big influence the quality of services provided to the satisfaction of taxpayer, and (3) to determine the factors that influence quality of services provided. This study uses a quantitative approach with survey methods, with a total of 318 respondents taxpayer. The result shows there is significant influence between each variable quality of service and simultaneously (shared) to the satisfaction of taxpayers. The contribution of variable reliability to the satisfaction of taxpayers amounted to 16.6%, for the variable responsiveness has the effect of 16.8%, for the variable assurance amounted to 20.7%, for the variable of empathy is at 33.7%, and for variable tangibles has the effect of 46.1%. Impact of service quality simultaneously (reliability, responsiveness, assurance, empathy, and tangibles) to satisfaction of taxpayers amounted to 51.4%. While for the other 48.6% influenced by other variables. Other factors that influence service quality to satisfaction of taxpayers are external factors such as community demands, and internal factors namely the Polri Bureaucratic Reform factor and Balikpapan SAMSAT service system changes such as changes in service procedures and application of ISO 9001:2008 Quality Management System